Past, Present, and Future: Editorial on Virtual Reality Applications to Human Services. Issue 1 (2nd January 2019) - Trahan, Mark H.; Smith, Kenneth Scott; Talbot, Thomas B.
Abstract: "Virtual Reality" interventions in human services may include 360° video, augmented reality, mixed reality, and fully immersive 3-dimensional virtual reality simulations. A variety of applications have been evaluated in various fields of study, including medicine, social work, psychology, and human performance training. Currently, the state of research of VR interventions in human services has primarily focused on efficacy and effectiveness research, with few studies evaluating "scaling up" or implementation of VR interventions in larger populations. Unfortunately, the state of efficacy and effectiveness studies of VR interventions still remains weak with some applications due to smaller sample sizes, lack of randomized control trials, and a gap in reporting key intervention qualities, dosage, and outcomes. With new developments in combining artificial intelligence with VR, realism and the potential for human interaction with computer generated simulations may boost presence and immersion within these applications. This editorial provides an overview of the state of virtual reality applications in human service provision, potential gaps to be addressed by research in the future, and the development of AI based interactive sequences that may boost use presence.